Sosialisasi untuk Pengembangan Website Klasifikasi Sampah Dinas Lingkungan Hidup dan Kebersihan (DLHK) di Kota Depok - Sari Ningsih; Panca Dewi Pamungkasari; Asrul Sani; Erina Rahmazani; Lili Dwi Yulianto; Ferdiansyah Ferdiansyah; Ghina Rahma; Muhammad Mustaqim; Muhammad Rangga (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service Program (PKM) aims to enhance the understanding of the staff at the Environmental and Sanitation Agency (DLHK) of Depok City in utilizing information technology through socialization and training on the development of a waste classification website. The website is designed to assist the public in identifying types of waste and to encourage more responsible and integrated waste management practices. The implementation methods for this program include socialization sessions, technical training workshops, and system usage demonstrations. Participants were introduced to the functionalities of the website, including how to classify various waste types and its role in supporting environmental sustainability. The program also provided hands-on training to ensure the staff could effectively use the website and incorporate it into their daily tasks. As a result, the staff’s understanding of the concept of digital-based waste classification has significantly increased. Additionally, the potential benefits of using such technology to support sustainable environmental management programs were clearly recognized. The program not only enhanced the staff's technical skills but also contributed to a deeper understanding of the importance of waste classification in the broader context of environmental conservation. The outcomes of this initiative are expected to encourage the staff to actively promote the use of the website to the public, thus fostering a more responsible and efficient waste management system in Depok City. This program demonstrates the effectiveness of integrating technology in supporting local government initiatives aimed at improving environmental management and sustainability. Furthermore, it underscores the importance of digital tools in modernizing waste management systems and enhancing public awareness and engagement.